Peripheral Classic and Intermediate Monocyte Subsets as Immune Biomarkers of Systemic Lupus Erythematosus Disease Activity - Amaylia Oehadian; Mohammad Ghozali; Sutiadi Kusuma; Lusi Mersiana; Nadia Gita Ghassani; Fransisca Fransisca; Yitzchak Millenard Sigilipu; Andini Kartikasari; Laniyati Hamijoyo (Acta Medica Indonesiana)
Background: Monocytes are evolutionarily preserved innate immune cells that play essential roles in immune response regulation. Three activated monocyte subsets—classical (CD14++CD16–), intermediate (CD14++CD16+), and nonclassical (CD14+CD16++)—are associated with systemic lupus erythematosus (SLE) progression. This study aims to determine the association of monocyte subsets with SLE disease activity. Methods: A cross-sectional study involving 25 patients with SLE was conducted. Blood samples were collected, and monocyte subsets were identified using flow cytometry. Patients were grouped by disease activity using the Systemic Lupus Erythematosus Disease Activity Index 2000 (SLEDAI-2K) into inactive (SLEDAI-2K ≤ 4) and active (SLEDAI-2K > 4). The cutoff for monocyte subsets was determined using Receiver Operating Characteristic (ROC) analysis. Results: Nine active and 16 inactive subjects were identified. Compared with individuals without active disease, individuals with active disease had significantly lower mean classical monocyte subsets (71.9% vs 88%, p = 0.008), and higher median intermediate monocytes (29.1% vs 11.1%, p = 0.019). The median nonclassical monocyte subsets were not significantly different between the two groups. The cutoff for classical monocytes in active disease was ≤72.2%, AUC = 0.788, p = 0.021, with 66.7% sensitivity and 87.5% specificity; for intermediate monocytes, it was >22.3%, AUC = 0.788, p = 0.014, with 66.7% sensitivity and 100% specificity. Conclusion: Classical and intermediate monocytes could be considered as immune cellular markers for identifying active SLE.